Anchoring of inflation expectations in the euro area: recent evidence based on survey data - Tomasz Łyziak; Maritta Paloviita (European Central Bank (ECB), 2016)
The paper analyses the anchoring of inflation expectations of professional forecasters and consumers in the euro area. We study anchoring, defined as the central bank's ability to manage expectations, by paying special attention to the impact of the ECB inflation target and ECB inflation projections on inflation expectations. Our analysis indicates that longer-term inflation forecasts have become somewhat more sensitive to shorter-term forecasts and to actual HICP inflation in the post-crisis period. We also find that the ECB inflation projections have recently become more important for short- and medium-term professional forecasts and at the same time the role of the ECB inflation target for those expectations has diminished. Overall, our analysis suggests that in recent years inflation expectations in the euro area have shown some signs of de-anchoring.
Keywords: D84; E52; E58; 330; anchoring; euro area; financial crisis; inflation expectations; survey data